2017
DOI: 10.1186/s13039-017-0327-3
|View full text |Cite
|
Sign up to set email alerts
|

Combination of t(4;14), del(17p13), del(1p32) and 1q21 gain FISH probes identifies clonal heterogeneity and enhances the detection of adverse cytogenetic profiles in 233 newly diagnosed multiple myeloma

Abstract: BackgroundOur aim was to set the FISH combination of del(17p13), t(4;14), 1q21 gain and del(1p32), four adverse cytogenetic factors rarely evaluated together, and compare our technical thresholds with those defined in the literature.MethodsTwo hundred thirty-three patients with MM at diagnosis were studied using FISH to target 4 unfavorable cytogenetic abnormalities: 17p13 deletion, t(4;14) translocation, 1p32 deletion and 1q21 gain. Technical thresholds were determined for each probe using isolated CD138-expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
1
7
2
Order By: Relevance
“…Previous studies have found that 1q21 gain was one of the most frequent chromosomal aberrations in MM, with the occurrence rate of about 30% to 50%. 14,[21][22][23] In the present study, 1q21 gain could be identified in 39.7% of all 446 patients, which is consistent with previously published studies. Thus, the biological characteristics and prognostic effect of 1q21 gain need to be investigated.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have found that 1q21 gain was one of the most frequent chromosomal aberrations in MM, with the occurrence rate of about 30% to 50%. 14,[21][22][23] In the present study, 1q21 gain could be identified in 39.7% of all 446 patients, which is consistent with previously published studies. Thus, the biological characteristics and prognostic effect of 1q21 gain need to be investigated.…”
Section: Discussionsupporting
confidence: 93%
“…Gain of 1q21 and deletions of 17p13, 8p21, and 13q14, on the contrary, were consistently more frequently detected in subclones, suggesting a role as secondary and progression-related aberrations. Thus, the subclone architecture of plasma cell dyscrasia in AL closely resembles that in myeloma, 9,11,35,36 8,37 We conclude that the lower subclone frequency in AL amyloidosis is a reflection of the high t(11;14) frequency, as well as the universal low propensity of t(11;14) for developing genetic subclones, rather than an AL amyloidosis-specific effect.…”
Section: Discussionmentioning
confidence: 66%
“…16 Nevertheless, they rarely have been analyzed together. [17][18][19] Today, the definition of cytogenetic risk profile in patients with MM, on the basis of two or three unfavorable prognostic markers, seems restrictive and oversimplified. We aimed to adapt MM treatment to risk by defining a cytogenetic risk classification that could be used systematically (hence routinely).…”
Section: Introductionmentioning
confidence: 99%